New Magnetotelluric Data Reveal Deep Fault Boundaries and Contrasting Late Cenozoic Fault Kinematics Between the Qilian Shan Thrust Wedge and Beishan‐Alxa Block, Western China - Haibo Yang; Xiangyu Sun; Yan Zhan; Xiaoping Yang; Dickson Cunningham; Lingqiang Zhao; Yuqi Zuo (Geophysical Research Letters, 2024)
Abstract The structural connectivity and kinematic relationship between the Altyn Tagh sinistral strike‐slip fault (ATF) and Qilian Shan fold‐and‐thrust belt along the north Tibetan margin east of 96°E is an important question for tectonicists interested in the evolving active deformation field of Central Asia and associated earthquake hazards of China's Hexi Corridor region. New results from a detailed 130‐km‐long N‐S magnetotelluric (MT) survey from the Qilian Shan to Beishan elucidates the locations and down‐dip orientations of major faults. Importantly, the results indicate that the Heishan‐Jinta’Nanshan fault system roots steeply into the lower crust, is unconnected to the Qilian Shan thrust wedge, and has reactivated the margin of the North China Craton and an older, regional ductile shear belt. The structurally linked ATF‐Heishan‐Jinta’Nanshan system defines a fundamental kinematic boundary in central Asia between the NE directed Qilian Shan thrust belt to the south and the eastwardly extruding Beishan‐Alxa Block to the north.